PENGARUH KOMUNIKASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI MELALUI MANAJEMEN PELAYANAN PADA KANTOR DINAS PERHUBUNGAN PROVINSI SULAWESI SELATAN - Hendra Gunawan (Universitas Ichsan Sidenreng Rappang, 2023)
This study aims to analyze the effect of work communication and work environment on employee performance through service management at the Transportation Agency of South Sulawesi Province. This research applied a quantitative approach with an explanatory survey design. The sample consisted of 112 employees. Data were collected using a questionnaire and analyzed using Partial Least Squares Structural Equation Modeling. The findings indicate that work communication has a positive and significant effect on employee performance and service management. The work environment also has a positive and significant effect on employee performance and service management. Service management has a positive and significant effect on employee performance. Furthermore, service management mediates the effect of work communication and work environment on employee performance. The R-squared value indicates that the model adequately explains employee performance variation. These findings confirm that improving employee performance in transportation public service requires strong work communication, a supportive work environment, and well-managed service processes.